Herbal nanoparticles: A patent review (Asian Journal of Pharmaceutics (AJP), 2014)
Design and development of herbal nanoparticles has become a frontier research in the nanoformulation arena. To updateresearchers, an attempt has been made to review nanoformulation-based herbal patents. This article mainly coversherbal medicines are used for the treatment of cardiovascular diseases, Parkinsonism, pulmonary diseases, proliferativediseases, Alzheimer’s disease, diabetes, cancer therapy, anti-osteoporosis, and the like. It has been revealed that nanoparticlesof Curcumin have been widely designed to increase its bioavailability and for treatment of cancers like breast cancer, lungcancer, pancreatic cancer, and so on. The common nanoformulated herbal medicines are Panax ginseng, Curcuma longa, Silybummarianum, Withania somnifera, Gymnema sylvestre, Salvia miltiorrhiza, and the like, having a profound future potential.